Novel approach of Principal Component Analysis method to assess the national energy performance via Energy Trilemma Index. (November 2019) - Asbahi, Ahmed Abdulwali Mohammed Haidar Al; Gang, Feng Zhi; Iqbal, Wasim; Abass, Qaiser; Mohsin, Muhammad; Iram, Robina
Abstract: The World Energy Council releases the Energy Trilemma Index (ETI) report annually primarily to assess the energy performance of countries worldwide. Nevertheless, the varying preferences of the dimensions in the ETI between the countries are debatable. The objective of this study is weight allocation therefore this study presents two-fold contribution to comprehensively formulate all possible preferences under the interval assessment outcomes by employing the interval decision matrix followed by the Principal Component Analysis (PCA) to assess the national energy performance of top ten countries for the year 2015. Unlike the conventional methods, the significant advantage of PCA for index construction is that it does not allocate ad-hoc and subjective weights to different indicators. The obtained results were demonstrated by measurement of top ten countries energy performance based on ETI of 2015. Through the development of Energy Development Index, Norway was determined as the highest performing country among the top ten countries. This does not coincide with 2015's ETI which regarded Switzerland as the best performing country. Hence, the ranks are arguable. Further results reveals that there are considerable differences in the values of indicators among all countries. The obtained outcome is expected to aid the policy makers to understand the contribution of different indicators.